Trehalose preincubation increases mesenchymal (CD271+) stem cells post-cryopreservation viability (Medical Journal of Indonesia, 2016)
Background: Dimethyl sulfoxide (Me2SO) is a common cryoprotective agent widely used in cell preservation system. Me2SO is currently known to cause epigenetic changes which are critical in stem cells development and cellular differentiation. Therefore, it is imperative to develop cryopreservation techniques that protect cellular functions and avert Me2SO adverse effect. Trehalose was able to protect organism in extreme condition such as dehydration and cold. This study aimed to verify the protective effect of trehalose preincubation procedure in cryopreservation. Methods: The study was conducted using experimental design. Thawed mesenchymal (CD271+) stem cells from YARSI biorepository were used for the experiment. Trehalose preincubation was performed for 1 hour, internalized trehalose was confirmed by FTIR-ATR measurement. Three groups consisted of (1) cryopreserved without trehalose preincubation, (2) cryopreserved with trehalose preincubation, and (3) did not undergo cryopreservation were evaluated after 24 hours in LN2 for viability in culture. The absorbance from each group was measured at 450 nm. The analysis performed using paired student t test. Results: Viability of thawed mesenchymal (CD271+) stem cells that undergo trehalose preincubation prior cryopreservation was significantly higher (p<0.05) compared to group without trehalose preincubation. Higher viability observed between group with trehalose preincubation compared with controlled group suggests protection to trypsinization. Mesenchymal (CD271+) stem cells incubated for 1 hour in 100 mM trehalose supplemented medium results in 15% trehalose loading efficiency. Conclusion: These findings confirm the protective effect of trehalose preincubation in cryopreservation. Future research should be directed to elucidate the trehalose internalization mechanism and eventually the protective mechanism of trehalose in mammalian cell cryopreservation.